2013
DOI: 10.1007/s00056-013-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Survey of oral health-related quality of life among skeletal malocclusion patients following orthodontic treatment and orthognathic surgery

Abstract: Our skeletal malocclusion questionnaire provides useful additional information on specific aspects of skeletal malocclusion patients, mapping in a detailed fashion aspects of function, esthetics, psychological condition, and social interactions. OHIP-G14 scores correlated negatively with OHRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
5
0
5
Order By: Relevance
“…In the future it is interesting to see how treatment affects patients' wellbeing. For example, in the studies by Al-Ahmad et al [38] and Lee et al [39], patients' OQoL improved posttreatment, while the results by Schmidt et al [40] suggest that some patients are still not satisfied with their aesthetic and functional outcomes, suffer from psychological difficulties, and withdraw from social life. Therefore, it is important not to focus solely on group differences between patients and controls, but to also include within-group comparisons to find those patients who do not benefit from treatment as much as they expected.…”
Section: Discussionmentioning
confidence: 92%
“…In the future it is interesting to see how treatment affects patients' wellbeing. For example, in the studies by Al-Ahmad et al [38] and Lee et al [39], patients' OQoL improved posttreatment, while the results by Schmidt et al [40] suggest that some patients are still not satisfied with their aesthetic and functional outcomes, suffer from psychological difficulties, and withdraw from social life. Therefore, it is important not to focus solely on group differences between patients and controls, but to also include within-group comparisons to find those patients who do not benefit from treatment as much as they expected.…”
Section: Discussionmentioning
confidence: 92%
“…1 The motivating factors for undergoing orthodontic treatment are enhanced dental and facial esthetics and, consequently, minimized psychosocial problems, which contribute to QoL. 2,3 Many studies [4][5][6][7] have explored the physical, social, or psychological effects of orthodontic treatment and how discomfort and pain affect these aspects of QoL. [4][5][6][7] It was found that depending on the phase of the treatment, orthodontic treatment may either compromise or improve oral health-related quality of life (OHRQoL).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of how facial appearance affects quality of life has rapidly increased the demand for such treatment. In most cases, the motivating factors for undergoing orthodontic treatment are enhanced dental and facial aesthetics and consequently minimized psychosocial problems 2,3. Studies of oral health-related quality of life (OHRQoL) in orthodontics are important because they provide information about therapeutic needs and outcomes as well as long-term oral health improvement 4.…”
Section: Introductionmentioning
confidence: 99%